Formalin Borax and Rhodamin Quick Detection Instruments Discovered by Researcher and Education Staff of Brawijaya University Produced By Biochem Laboratory - Chanif Mahdi (Jurnal VOK@SINDO, 2013)
Formalin borax and rhodamin are toxic and carcinogenic substances which could cause cells damage in short term, and could cause 50 kond of degenerative disease and cancer in long term. The aims of this study are to know the potent and effectiveness of three of instruments of reagent kit testers: Formalin main reagent (FMR), Borax main reagent (BMR) and Colour main reagent (CMR) to detect formalin, borax and rhodamin on food, and to know the content of formalin, borax and rhodamin on food recently. The result of the study showed that quick detection instruments of reagent kit tester produced by BioChem laboratory are effective and efficient to detect formalin, borax and rhodamin on food, with limit potent minimal concentration detection were 5 ppm or less, in not more 10 minutes periods. The result of the study also showed that formalin borax and rhodamin still can be found in many kinds of food distributed in area of Malang.